Isolation and identification of polysaccharide (gum)-producing bacteria from a sugarcane factory and strategies to prevent their growth - Nel, Sanet (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.